FINANCIAL MATHEMATICS TEACHING IN THE UNIVERSITY - Hidalgo Tupia, Manuel Alberto (2016)
This article presents the results of the research entitled “Application effects of an active, relevant and heuristic methodology in the learning of mathematical finance” developed by the author for obtaining the degree of Doctor in Education, defended on November 2015, in the Graduate School of Education of the Universidad Nacional Mayor de San Marcos.The research involved the study of the pedagogy ́s fundamentals applied to the teaching of mathematics, like in the case of applied mathematics, specifically, financial mathematics. The desirable features of a teaching methodology for financial mathematics were sought, within the existing theoretical approach. On that base, a teaching methodology was formulated, centered on the characteristics of activism, relevance, and heuristics; and then applied in teaching course in the Universidad de Lima, to finally measure the effect on student learning. The treatment was applied to an experimental group and also to a control group, in the course of two years, plus the results were recorded. The hypothesis was statistically tested and the results support it. They show the effect of the teaching methodology, which was widely described in its foundations, conditions, strategies, planning training sessions, materials and evaluation.